Percutaneous radiofrequency ablation of hepatocellular carcinomas abutting the right posterior diaphragm: factors associated with tumor recurrence and overall survival - Lee, Ji Soo; Ahn, Soo Hyun; Lee, Min Woo; Han, Seungchul; Min, Ji Hye; Cha, Dong Ik; Song, Kyoung Doo; Kang, Tae Wook; Rhim, Hyunchul (Acta Radiologica, 2025)
Background: Radiofrequency ablation (RFA) of subphrenic hepatocellular carcinomas (HCCs) using ultrasound (US) guidance presents a challenge. Purpose: To evaluate local tumor progression (LTP) and overall survival (OS) after RFA of right posterior subphrenic HCCs, and to identify the risk factors for LTP and OS after RFA. Material and Methods: We screened patients who underwent US-guided RFA for a single HCC <3 cm in the right posterior subphrenic area. Cumulative rates of LTP and OS were compared between multiple- and single-electrode treatments and artificial pleural effusion versus no-effusion groups using Kaplan–Meier curves and the log-rank test. The risk factors for LTP and OS were assessed. Results: A total of 36 patients were included. The cumulative 5-year and 10-year LTP rates were 32.9% and 39.6%, respectively, and the corresponding OS rates were 72.2% and 48.7%, respectively. The multiple-electrode group had significantly lower cumulative LTP rates compared to the single-electrode group (P < 0.001). The group receiving artificial pleural effusion showed a trend towards lower LTP rates than the no-effusion group (P = 0.076). The albumin-bilirubin (ALBI) grade was the only risk factor for LTP (hazard ratio [HR] = 4.17, 95% confidence interval [CI] = 1.26–14.55; P = 0.020). A lower albumin level was a risk factor for mortality (HR = 0.24, 95% CI = 0.07–0.79; P = 0.020). Conclusion: US-guided RFA with multiple electrodes and artificial pleural effusion tends to be linked with lower LTP rates. The ALBI grade and serum albumin level are risk factors for LTP and OS, respectively.
Keywords: Artificial pleural effusion; Hepatocellular carcinoma; Local tumor progressions; Multiple electrodes; Overall survival; Pleural effusion; Radiofrequency ablation; Risk factors; Single electrodes; Ultrasound-guided; Aged; Carcinoma, Hepatocellular; Diaphragm; Female; Humans; Liver Neoplasms; Male; Middle Aged; Neoplasm Recurrence, Local; Radiofrequency Ablation; Retrospective Studies; Risk Factors; Survival Rate; Treatment Outcome; Ultrasonography, Interventional; artificial pleural effusion; diaphragm; hepatocellular carcinoma; local tumor progression; Radiofrequency ablation